International Commodity Prices and Civil War Outbreak: New Evidence for Sub-Saharan Africa and Beyond - Antonio Ciccone (Center for Economic Studies and ifo Institute (CESifo), 2018)
A new dataset by Bazzi and Blattman (2014) allows examining the effects of international commodity prices on the risk of civil war outbreak with more comprehensive data. I find that international commodity price downturns sparked civil wars in Sub-Saharan Africa. Another finding with the new dataset is that commodity price downturns also sparked civil wars beyond Sub-Saharan Africa since 1980. Effects are sizable relative to the baseline risk of civil war outbreak. My conclusions contrast with those of Bazzi and Blattman, who argue that the new dataset rejects that commodity price downturns cause civil wars. The reason is that I calculate commodity price shocks using time-invariant (fixed) export shares as commodity weights. Bazzi and Blattman also calculate commodity price shocks using export shares as commodity weights but the exports shares they use are time-varying. Using time-invariant export shares as commodity weights ensures that time variation in price shocks solely reflects changes in international commodity prices. Price shocks based on time-varying export shares partly reflect (possibly endogenous) changes in the quantity and variety of countries' exports, which jeopardizes causal estimation. I also show that setting time-invariant export shares equal to average export shares over the sample period, can be a way of dealing with attenuation bias due to mismeasured export shares. When I differentiate between agricultural commodities on the one hand and minerals, oil, and gas on the other, I find stronger increases in the risk of civil war outbreak following downturns in agricultural commodity prices.
Keywords: E30; 330; civil wars; commodity price downturn